Persepsi Masyarakat Desa Situgede Kota Bogor terhadap Daging Sapi Beku Impor dan Daging Sapi Segar Lokal - Amelia Friska Pertiwi; Mochammad Sriduresta Soenarno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Beef is one of a variety of food products that are considered to have good nutrition for the protein needs of the community. Fresh meat is meat that has not been processed and or not added to any ingredient. Frozen meat is fresh meat that has undergone a freezing process in a blast freezer with a minimum internal temperature of -18 ° C. The purpose of this study was to determine perception of situgede village, bogor city on imported frozen beef and local fresh beef. The method used was interviewing informants of 16 random housewives in 10 RW and literature review. The data obtained were then analyzed using descriptive analysis. The results of the interviews with all the interviewees were of the opinion that imported frozen beef is pale, the texture of the meat is rather coarse, fat (marbling) a lot and white, it does not absorb seasonings after cooking a lot of fat so it becomes juicy, the aroma does not smell. While local beef is fresh, the color of fresh red meat, large fibrous texture, little fat (marbling), the taste of meat, the aroma of meat does not smell foul. The physical quality of imported frozen beef is better than fresh local beef and the price is cheaper. However, people prefer local fresh beef. This is because the purpose of cooking the community in Situgede is cooked in a long time, namely rendang, stews etc. Further research needs to be done on the physical and chemical characteristics of imported frozen beef and local fresh beef, providing knowledge and socialization about the physical and chemical quality of imported beef so that people know the true quality of the meat. Keywords: community perception, imported frozen beef, local fresh meat